Comparison with others of university students - saloom, Huda saad; Al-Daqhstani, Sana Essa Muhammed (Al-Adab Journal, 2021)
Researchers have expanded the concept of comparison with others to include material properties to determine the relative position of the individuals as well as compare opinions, experiences, emotions, and responses towards situations experienced by the individuals. the current research sample of (400) male and female students :(200) male and (200) female. they were randomly chosen from eight colleges, and to achieve the goals of the current research, the researcher adopted the festingers social comparison theory (1954) to explain the comparison with others. the reliability coefficient of comparison with others scale is (0,72) The current research reached the following conclusion: 1- University students display low of comparison with others.2- there are differences in comparison with others according to the gender variable in favor of females. This is due to that the calculated of alpha value of (7,82) is higher than the tabular value of (3,84) at the level of (0,05) and the degree of freedom (1-396) providing psychological guidance by mentors to spread rational thoughts and encourage avoiding useless or negative comparisons that reduce the importance of the human being). The researcher suggested several proposals, including: conducting a study on the relationship between fear and social comparison.